Terrestrial Education and Marine Structural Design: A Post-Sustainability Framework for Ocean Engineering Innovation - Del Mastro, Antonio; Garofalo, Giovanni; Veragouth, Pietro (Sustainable Marine Structures, 2025)
This paper argues that in an era of accelerating climate change and rising sea levels, what truly matters is not merely the marine structure itself, but the foresight and adaptability embedded in its conception. As global urbanization intensifies along coastlines, and as storms grow stronger and ecosystems degrade, there is an urgent need for transformative approaches to ocean engineering and design. We introduce Terrestrial Education, an interdisciplinary framework that moves beyond conventional sustainability models by integrating ecological intelligence, regenerative systems thinking, and advanced technologies. Unlike traditional approaches that focus on minimizing harm, Terrestrial Education emphasizes active ecological restoration, socio-technical evolution, and planetary stewardship. Drawing on lessons from space exploration, such as closed-loop life support systems, autonomous environmental management, and modular habitat design, we demonstrate how these principles can inspire resilient marine infrastructures, including floating platforms, submerged laboratories, and bio-integrated offshore structures. These designs are envisioned not only for their physical durability but also for their capacity to regenerate ecosystems and foster meaningful human interaction with marine environments. The paper highlights key priorities such as adaptability to climate extremes, energy efficiency through marine renewables, and environmental integration using biomimetic materials. By aligning with the Sustainable Development Goals of the blue economy, Terrestrial Education offers a future-oriented model that harmonizes environmental, technological, and economic objectives. Ultimately, this framework provides a conceptual and operational foundation for reimagining marine structures as catalysts for innovation, educational transformation, and resilient planetary futures in the climate era. ER